A global overview of studies about land management, land‐use change, and climate change effects on soil organic carbon. (7th December 2021) - Beillouin, Damien; Cardinael, Rémi; Berre, David; Boyer, Annie; Corbeels, Marc; Fallot, Abigail; Feder, Frédéric; Demenois, Julien
Abstract: Major drivers of gains or losses in soil organic carbon (SOC) include land management, land‐use change, and climate change. Thousands of original studies have focused on these drivers of SOC change and are now compiled in a growing number of meta‐analyses. To critically assess the research efforts in this domain, we retrieved and characterized 192 meta‐analyses of SOC stocks or concentrations. These meta‐analyses comprise more than 13, 200 original studies conducted from 1910 to 2020 in 150 countries. First, we show that, despite a growing number of studies over time, the geographical coverage of studies is limited. For example, the effect of land management, land‐use change, and climate change on SOC has been only occasionally studied in North and Central Africa, and in the Middle East and Central Asia. Second, the meta‐analyses investigated a limited number of land management practices, mostly mineral fertilization, organic amendments, and tillage. Third, the meta‐analyses demonstrated relatively low quality and transparency. Lastly, we discuss the mismatch between the increasing number of studies and the need for more local, reusable, and diversified knowledge on how to preserve high SOC stocks or restore depleted SOC stocks. Abstract : We present a global overview of 192 meta‐analyses of SOC compiling 13, 270 original studies. We highlighted a mismatch between the available evidence and geographic regions with high SOC stocks or high carbon storage potential. Most of the meta‐analyses focused on a limited number of land management practices. These knowledge gaps may hinder the formulation of evidence‐based recommendations to promote SOC sequestration practices. This synthesis is a call to the soil science community to diversify the portfolio of options that allow increasing or preserving SOC stocks, and to prioritize studies in overlooked regions, such as in Africa.